Open e-learning platforms and the design–reality gap: an affordance theory perspective. Issue 8 (22nd December 2021) - McCarthy, Stephen; Rowan, Wendy; Kahma, Nina; Lynch, Laura; Ertiö, Titiana Petra
Abstract : Purpose: The dropout rates of open e-learning platforms are often cited as high as 97%, with many users discontinuing their use after initial acceptance. This study aims to explore this anomaly through the lens of affordances theory, revealing design–reality gaps between users' diverse goals and the possibilities for action provided by an open IT artefact. Design/methodology/approach: A six-month case study was undertaken to investigate the design implications of user-perceived affordances in an EU sustainability project which developed an open e-learning platform for citizens to improve their household energy efficiency. Thematic analysis was used to reveal the challenges of user continuance behaviour based on how an open IT artefact supports users in achieving individual goals (e.g. reducing energy consumption in the home) and collective goals (lessening the carbon footprint of society). Findings: Based on the findings, the authors inductively reveal seven affordances related to open e-learning platforms: informing, assessment, synthesis, emphasis, clarity, learning pathway and goal-planning. The findings centre on users' perception of these affordances, and the extent to which the open IT artefact catered to the goals and constraints of diverse user groups. Open IT platform development is further discussed from an iterative and collaborative perspective in order to explore different possibilities for action. Originality/value: The study contributes towards research on open IT artefact design by presenting key learnings on how the designers of e-learning platforms can bridge design–reality gaps through exploring affordance personalisation for diverse user groups. This can inform the design of open IT artefacts to help ensure that system features match the expectations and contextual constraints of users through clear action-oriented possibilities.